A method for preparing aerospace-grade vanadium-aluminum alloy with low oxygen content
Patent Information
- Application Number
- CN202310933568.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-27
- Publication Date
- 2026-10-30
- Estimated Expiration
- 2043-07-27
AI Technical Summary
钒铝合金的制备通常采用铝热法,即采用Al还原V2O5制备出钒铝合金,由于铝热还原反应是在大气环境下进行的,根据V-Al相图,当V含量为50~60wt%时,随着合金熔液的冷却,先析出Al8V5相,再析出AlV3相,由于Al8V5相的脆性特点,当AlV3相析出时产生局部应力,导致Al8V5相产生裂隙,而且由于在大气环境中制备,空气中的氧进入到合金内部,与Al8V5产生氧化、氮化反应,生成淡黄色、黄色、蓝紫色氧化膜,导致AIV55合金的氧含量较高,影响产品的外观质量,并容易使最终制备的钛合金开裂
[0014]1、本发明在制备AlV55合金时,利用少量不容易氧化的AlV65合金完全覆盖住暴露在空气中容易氧化的AlV55合金,使其在极易氧化的温度(700~1670℃)下,无法与大气中的氧气接触,从而可以降低AlV55合金中的氧含量,作为保护层的AlV65合金被喷砂处理掉,最终成品中的氧含量极低,保证最终制成的钒铝合金成分符合航空航天等高端领域的应用要求;
Smart Images

Figure CN116770072B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of titanium master alloy preparation technology, specifically relating to a method for preparing aerospace-grade vanadium-aluminum alloy with low oxygen content. Background Technology
[0002] Vanadium-aluminum alloys are essential materials for the preparation of high-temperature, high-strength titanium alloys for aerospace applications, and their quality directly affects the overall performance of the titanium alloys. Vanadium-aluminum alloys are classified into the following grades based on their vanadium (V) content: AlV55 (V content 50–60 wt%), AlV65 (V content > 60–70 wt%), AlV75 (V content > 70–80 wt%), and AlV85 (V content > 80–90 wt%). The preparation of vanadium-aluminum alloys typically employs the aluminothermic process, which involves the reduction of V₂O₅ by Al. Since the aluminothermic reduction reaction occurs in an atmospheric environment, according to the V-Al phase diagram, when the V content is 50–60 wt%, the Al₈V₅ phase precipitates first, followed by the Al₂V₃ phase, as the alloy melt cools. Due to the brittle nature of the Al₈V₅ phase, the precipitation of Al₂V₃ generates localized stress, leading to cracks in the Al₈V₅ phase. Furthermore, because the preparation takes place in an atmospheric environment, oxygen from the air enters the alloy's interior, reacting with Al₈V₅ to produce oxidation and nitriding reactions, generating pale yellow, yellow, and bluish-purple oxide films. This results in a high oxygen content in the AIV₅ alloy, affecting the product's appearance quality and making the final titanium alloy prone to cracking. Common methods to inhibit oxidation include vacuum melting and argon atmosphere-protected melting. Both methods place high demands on the airtightness of the production equipment, making them unsuitable for industrial-scale production. Summary of the Invention
[0003] To address the aforementioned problems in the prior art, this invention provides a method for preparing aerospace-grade vanadium-aluminum alloys with low oxygen content. The technical problem to be solved by this invention is achieved through the following technical solution:
[0004] A method for preparing aerospace-grade vanadium-aluminum alloy with low oxygen content, comprising:
[0005] Step 1: Dry the V2O5 and Al chips separately;
[0006] Step 2: Mix V2O5 and Al chips at a mass ratio of (0.95~1.15):1 to obtain the first mixture; mix V2O5 and Al chips at a mass ratio of (1.16~1.80):1 to obtain the second mixture;
[0007] Step 3: Add the first mixture into the crucible, ignite and carry out the aluminothermic reduction reaction to obtain the first vanadium-aluminum alloy in molten state, wherein the V content is 50-60 wt%.
[0008] Step 4: When the reaction temperature in the crucible drops to 1670-1700℃, after the molten first vanadium-aluminum alloy surface layer solidifies, the second mixture is added to completely cover the first vanadium-aluminum alloy surface layer. The second mixture is ignited to carry out an aluminothermic reduction reaction to obtain a molten second vanadium-aluminum alloy. The molten second vanadium-aluminum alloy seals the surface layer of the first vanadium-aluminum alloy, thereby isolating the first vanadium-aluminum alloy from the air.
[0009] Step 5: After the reaction is complete, allow it to cool naturally, then remove the slag and the second vanadium-aluminum alloy. The remaining first vanadium-aluminum alloy is the low-oxygen vanadium-aluminum alloy.
[0010] Furthermore, in step 1, V2O5 and Al chips are dried separately at a temperature of 100–120°C for 48–72 hours.
[0011] Preferably, V2O5 and Al chips are mixed at a mass ratio of (1.16 to 1.25):1 to obtain the second mixture.
[0012] Furthermore, the thickness of the molten second vanadium-aluminum alloy is 5–8 mm.
[0013] The beneficial effects of this invention are:
[0014] 1. In the preparation of AlV55 alloy, this invention uses a small amount of AlV65 alloy, which is not easily oxidized, to completely cover the AlV55 alloy that is easily oxidized when exposed to air. This prevents the AlV55 alloy from coming into contact with atmospheric oxygen at temperatures that are highly prone to oxidation (700-1670°C), thereby reducing the oxygen content in the AlV55 alloy. The AlV65 alloy, which serves as a protective layer, is then sandblasted away. The final product has an extremely low oxygen content, ensuring that the composition of the final vanadium-aluminum alloy meets the application requirements of high-end fields such as aerospace.
[0015] 2. Compared with vacuum melting technology, this invention does not involve the use of vacuum equipment, has no requirements for the airtightness of the reaction device, does not change the existing production equipment, has low process optimization costs, and is suitable for industrial-scale production; compared with argon atmosphere protection technology, this invention does not involve protective atmosphere devices and pressure devices, does not require the installation of atmosphere protection covers, can be carried out in an atmospheric environment, does not change the existing production equipment, and has low process optimization costs; it only requires two small feedings, utilizing the difference in alloy phase composition, that is, utilizing the strength and density of the protective layer, to protect the produced AlV55 alloy from oxidation.
[0016] The present invention will be further described in detail below with reference to the accompanying drawings and embodiments. Attached Figure Description
[0017] Figure 1 This is a photograph taken after the final reaction of the present invention has concluded;
[0018] Figure 2 The oxygen content of vanadium-aluminum alloys as specified in national standards;
[0019] Figure 3 The test report for the low-oxygen AlV55 alloy prepared in Example 1;
[0020] Figure 4 A photograph of the AlV55 alloy prepared using the method in Comparative Example 1;
[0021] Figure 5 The test report for the low-oxygen AlV55 alloy prepared in Example 2;
[0022] Figure 6 A photograph of the AlV55 alloy prepared using the method in Comparative Example 2. Detailed Implementation
[0023] The following is combined with Figures 1-6 The present invention will be further described in detail with reference to specific embodiments, but the implementation of the present invention is not limited thereto.
[0024] Example 1
[0025] This invention provides a method for preparing aerospace-grade vanadium-aluminum alloy with a low oxygen content and a V content of 55 wt%, specifically including the following steps:
[0026] Step 1: Dry the V2O5 and Al chips separately.
[0027] Specifically, V2O5 and Al chips were dried separately in stainless steel trays at a temperature of 100°C for 72 hours.
[0028] Since there is bound water on the surface of V2O5 and Al chips, the water needs to absorb a certain amount of heat during subsequent ignition, resulting in a low initial calorific value of the reaction, which slows down the reaction and may even cause the reaction to stop. Therefore, after mixing the two raw materials, the water in the raw materials is evaporated to increase the initial calorific value of the reaction.
[0029] Step 2: Weigh 128 kg of V2O5 and 122 kg of Al chips and mix them evenly to obtain the first mixture; mix 5 kg of V2O5 and 3.98 kg of Al chips evenly to obtain the second mixture.
[0030] Step 3: Add the first mixture into a graphite crucible, use Mg strip as an ignition agent to ignite the surface of the first mixture, and carry out an aluminothermic reduction reaction. After the aluminothermic reduction reaction is completed, a molten first vanadium-aluminum alloy with a V content of 55wt% is obtained.
[0031] Step 4: When the reaction temperature inside the crucible drops to 1670℃, after the surface layer of the molten first vanadium-aluminum alloy solidifies, the second mixture is added to completely cover the surface layer of the first vanadium-aluminum alloy. The second mixture is evenly spread on the outer surface of the portion of the first vanadium-aluminum alloy exposed in the crucible, ensuring that it completely covers the exposed portion. The temperature of the surface layer of the first vanadium-aluminum alloy is used to initiate a new round of aluminothermic reduction reaction, thereby obtaining a molten second vanadium-aluminum alloy with a V content of 65wt% on the solid surface layer of the first vanadium-aluminum alloy. The thickness of the molten second vanadium-aluminum alloy is 5mm, and the molten second vanadium-aluminum alloy completely encapsulates the exposed portion of the first vanadium-aluminum alloy in the crucible. The molten second vanadium-aluminum alloy seals the surface layer of the first vanadium-aluminum alloy, thus isolating the first vanadium-aluminum alloy from the air.
[0032] Because the V content in the second vanadium-aluminum alloy exceeds 60wt%, and the internal phase composition of the alloy is singular (only Al8V5 phase), it is compact and dense, making it difficult for oxygen in the air to enter the interior of the alloy and cause oxidation. This also prevents air from entering the first vanadium-aluminum alloy, thus avoiding oxidation of the first vanadium-aluminum alloy.
[0033] Furthermore, since the second mixture is located on the outer surface of the first vanadium-aluminum alloy, when it undergoes an aluminothermic reduction reaction, the reaction temperature will exceed the liquidus line of the first vanadium-aluminum alloy, causing the outermost alloy of the first vanadium-aluminum alloy to become miscible with the second mixture. Ultimately, an extremely thin transition layer is formed between the second vanadium-aluminum alloy and the first vanadium-aluminum alloy. This transition layer is composed of Al8V5 and a very small amount of AlV3, which is then removed by sandblasting.
[0034] According to the V-Al phase diagram, an increase in V content leads to a shift in the liquidus line of the V-Al alloy, i.e., an increase in melting point. An increased melting point means the alloy solidifies more quickly during cooling, resulting in insufficient flow time for the second vanadium-aluminum alloy on the surface of the first vanadium-aluminum alloy. This leads to highly uneven distribution and poor coverage, allowing oxygen to enter the first vanadium-aluminum alloy through uncovered areas. Furthermore, high-V content alloys (AlV75, AlV85) require more V₂O₅ to form the same volume of alloy, resulting in higher costs and making them unsuitable for practical production. Therefore, in this invention, an AlV65 alloy is selected as the protective layer to isolate the first vanadium-aluminum alloy from air.
[0035] Step 5: After the reaction is complete and the alloy in the crucible cools naturally, the cooled vanadium-aluminum alloy block is removed from the crucible. Then, the transition layer, the second vanadium-aluminum alloy, and the slag on its surface are sandblasted to expose the first vanadium-aluminum alloy inside. This first vanadium-aluminum alloy is the low-oxygen AlV55 alloy. The elemental content of the alloy surface is detected using a handheld alloy analyzer to confirm that the elemental content meets the design value. After X-ray detection, the qualified AlV55 alloy is crushed and sieved. Then, samples are taken for chemical composition analysis. After the analysis is qualified, it is packaged and stored.
[0036] Comparative Example 1
[0037] Comparative Example 1 provides a conventional method for preparing a vanadium-aluminum alloy with a V content of 55 wt%, specifically including the following steps:
[0038] Step 1: Weigh 128 kg of V2O5 and 122 kg of Al chips, mix them evenly to obtain the aluminothermic reduction reaction mixture.
[0039] Step 2: Add the aluminothermic reduction reaction mixture into a graphite crucible, and use Mg strip as an ignition agent to ignite the surface of the first mixture to carry out the aluminothermic reduction reaction. After the aluminothermic reduction reaction is completed, a molten vanadium-aluminum alloy with a V content of 55wt% is obtained.
[0040] Step 3: After the reaction is complete and the alloy in the crucible has cooled naturally, remove the cooled AlV55 alloy block from the crucible, sandblast its surface, and then perform chemical element analysis.
[0041] The detection results of Example 1 and Comparative Example 1 are shown below:
[0042] Table 1. Chemical elemental analysis of the AlV55 alloys generated in Example 1 and Comparative Example 1.
[0043]
[0044] In Table 1, the testing of sample number 1 was completed by a third-party testing agency, and the corresponding test report is as follows: Figure 3 As shown, the data for samples 2 and 3, as well as Comparative Example 1, were obtained by the applicant in their laboratory using an alloy analyzer; as shown in Table 1 and Figure 2 , Figure 3 and Figure 4 It is evident that the method of this invention can significantly reduce the oxygen content of AlV55 alloy. While the oxygen content of AlV55 alloy obtained using conventional methods meets national standards, the oxygen content in the AlV55 alloy is far higher than that in Example 1 because its cooling process is completely exposed to air. Figure 4It can be seen that a layer of blue-purple oxide film is clearly formed on its surface, and its oxygen content is 0.176wt%, which is significantly higher than the oxygen content of the AlV55 alloy obtained by the method of the present invention.
[0045] Example 2
[0046] This invention provides a method for preparing a low-oxygen vanadium-aluminum alloy with a V content of 58 wt%, specifically including the following steps:
[0047] Step 1: Dry the V2O5 and Al chips separately.
[0048] Specifically, V2O5 and Al chips were dried separately in stainless steel pans at a temperature of 120°C for 48 hours.
[0049] Step 2: Weigh 132 kg of V2O5 and 118 kg of Al chips and mix them evenly to obtain the first mixture; mix 5 kg of V2O5 and 4.3 kg of Al chips evenly to obtain the second mixture.
[0050] Step 3: Add the first mixture into a graphite crucible, and use Mg strip as an ignition agent to ignite the surface of the first mixture to carry out an aluminothermic reduction reaction. After the aluminothermic reduction reaction is completed, a molten first vanadium-aluminum alloy with a V content of 58wt% is obtained.
[0051] Step 4: When the reaction temperature inside the crucible drops to 1700℃, after the surface layer of the molten first vanadium-aluminum alloy solidifies, the second mixture is added to completely cover the surface layer of the first vanadium-aluminum alloy. The second mixture is evenly spread on the outer surface of the portion of the first vanadium-aluminum alloy exposed in the crucible, ensuring that it completely covers the exposed portion. The temperature of the surface layer of the first vanadium-aluminum alloy is used to initiate a new round of aluminothermic reduction reaction, thereby obtaining a molten second vanadium-aluminum alloy with a V content of 60.6 wt% on the solid surface layer of the first vanadium-aluminum alloy. The thickness of the molten second vanadium-aluminum alloy is 6 mm, and the molten second vanadium-aluminum alloy completely encapsulates the exposed portion of the first vanadium-aluminum alloy in the crucible. The molten second vanadium-aluminum alloy seals the surface layer of the first vanadium-aluminum alloy, thus isolating the first vanadium-aluminum alloy from the air.
[0052] Step 5: After the reaction is complete and the alloy in the crucible cools naturally, the cooled vanadium-aluminum alloy block is removed from the crucible. Then, the transition layer, the second vanadium-aluminum alloy, and the slag on its surface are sandblasted to expose the first vanadium-aluminum alloy inside. This first vanadium-aluminum alloy is the low-oxygen AlV55 alloy. The elemental content of the alloy surface is detected using a handheld alloy analyzer to confirm that the elemental content meets the design value. After X-ray detection, the qualified AlV55 alloy is crushed and sieved. Then, samples are taken for chemical composition analysis. After the analysis is qualified, it is packaged and stored.
[0053] Comparative Example 2
[0054] Comparative Example 1 provides a conventional method for preparing a vanadium-aluminum alloy with a V content of 58 wt%, specifically including the following steps:
[0055] Step 1: Weigh 132 kg of V2O5 and 118 kg of Al chips, mix them evenly to obtain the aluminothermic reduction reaction mixture.
[0056] Step 2: Add the aluminothermic reduction reaction mixture into a graphite crucible, and use Mg strip as an ignition agent to ignite the surface of the first mixture to carry out the aluminothermic reduction reaction. After the aluminothermic reduction reaction is completed, a molten vanadium-aluminum alloy with a V content of 58wt% is obtained.
[0057] Step 3: After the reaction is complete and the alloy in the crucible has cooled naturally, remove the cooled AlV55 alloy block from the crucible, sandblast its surface, and then perform chemical element analysis.
[0058] The detection results of Example 2 and Comparative Example 2 are shown below:
[0059] Table 2. Chemical elemental analysis of the AlV55 alloys generated in Example 2 and Comparative Example 2.
[0060]
[0061] In Table 2, the testing of sample number 1 was completed by a third-party testing agency, and the corresponding test report is as follows: Figure 5 As shown, the data for samples 2 and 3, as well as Comparative Example 2, were obtained by the applicant in their laboratory using an alloy analyzer; as shown in Table 2 and Figure 2 , Figure 5 and Figure 6 It is known that the method of this application can significantly reduce the oxygen content of AlV55 alloy. While the oxygen content of AlV55 alloy obtained using conventional methods meets national standards, the oxygen content is far higher than that in Example 2 because the cooling process is completely exposed to air. Figure 6It can be seen that a layer of light yellow and blue-purple oxide film is clearly formed on its surface, and its oxygen content is 0.126 wt%, which is significantly higher than the oxygen content of the AlV55 alloy obtained by the method of the present invention.
[0062] In the description of this invention, the terms "first" and "second" are used for descriptive purposes only and should not be construed as indicating or implying relative importance or implicitly specifying the number of indicated technical features. Thus, a feature defined as "first" or "second" may explicitly or implicitly include one or more of that feature. In the description of this invention, "a number" means two or more, unless otherwise explicitly specified.
[0063] The above description, in conjunction with specific preferred embodiments, provides a further detailed explanation of the present invention. It should not be construed that the specific implementation of the present invention is limited to these descriptions. For those skilled in the art, various simple deductions or substitutions can be made without departing from the concept of the present invention, and all such modifications and substitutions should be considered within the scope of protection of the present invention.
Claims
1. A method for preparing aerospace-grade vanadium-aluminum alloy with low oxygen content, characterized in that, include: Step 1: Dry the V2O5 and Al chips separately; Step 2: Mix V2O5 and Al chips at a mass ratio of (0.95~1.15):1 to obtain the first mixture; mix V2O5 and Al chips at a mass ratio of (1.16~1.80):1 to obtain the second mixture; Step 3: Add the first mixture into the crucible, ignite and carry out the aluminothermic reduction reaction to obtain the first vanadium-aluminum alloy in molten state, wherein the V content is 50-60 wt%. Step 4: When the reaction temperature in the crucible drops to 1670-1700℃, after the molten first vanadium-aluminum alloy surface layer solidifies, the second mixture is added to completely cover the first vanadium-aluminum alloy surface layer, and the aluminothermic reduction reaction continues to obtain the molten second vanadium-aluminum alloy. The V content of the second vanadium-aluminum alloy is greater than 60wt%. The molten second vanadium-aluminum alloy seals the surface layer of the first vanadium-aluminum alloy, thereby isolating the first vanadium-aluminum alloy from the air. Step 5: After the reaction is complete, allow it to cool naturally, then remove the slag and the second vanadium-aluminum alloy. The remaining first vanadium-aluminum alloy is the low-oxygen vanadium-aluminum alloy.
2. The method for preparing aerospace-grade vanadium-aluminum alloy with low oxygen content according to claim 1, characterized in that, In step 1, V2O5 and Al chips are dried separately at a temperature of 100-120°C for 48-72 hours.
3. The method for preparing aerospace-grade vanadium-aluminum alloy with low oxygen content according to claim 1 or 2, characterized in that, The second mixture is obtained by mixing V2O5 and Al chips at a mass ratio of (1.16 to 1.25):
1.
4. The method for preparing aerospace-grade vanadium-aluminum alloy with low oxygen content according to claim 3, characterized in that, The thickness of the molten second vanadium-aluminum alloy is 5-8 mm.
Citation Information
Patent Citations
Vanadium-aluminum alloy production method
CN108330370A